“Complex” Vasovagal Syncope: A Zebra Among Horses - Siddiqi, Anwer Zohaib; Blackmore, Derrick; Siddiqi, Zaeem Azfer (Frontiers in Neurology, 2020)
Background: Vasovagal syncope (VVS) occurs due to cerebral hypoperfusion from a fall in blood pressure, with accompanying bradycardia in most cases. Seizure and/or asystole may accompany VVS, though their prediction within the VVS cohort remains elusive. Objective: To further characterize VVS and to find predictive features of “complex” VVS (defined as VVS associated with seizures and/or asystole). Methods: We reviewed medical records of all patients who were referred for orthostatic intolerance and had a definite VVS during the head-up tilt table testing (HUTT). The following variables were recorded: cardiovascular indices during HUTT, autonomic testing results, and semiology of asystole and/or seizure when present. Simple frequency and correlation analysis were performed using the ANOVA. Results: A total of 78 independent VVS were recorded in 60 patients of which 24% were not preceded by presyncope. Vasodepressor (45%) and mixed (38%) VVS were the most prevalent types. Eighteen (23%) were complex VVS; five had an associated seizure (SySz), nine were accompanied by asystole (SyAs), and four had both (SySzAs). Male were significantly more likely to have complex VVS. Mean asystole duration was somewhat longer in the SyAsSz group. The severity of bradycardia significantly correlated with complex VVS and was a predictor of SySz. Autonomic abnormalities were frequent but did not distinguish the two VVS subgroups. Seizures had multiple distinguishing features from those typically associated with epileptic seizures. Conclusions: The underlying pathophysiologic mechanisms of complex VVS remain unclear but the severity of cerebral hypoperfusion due to bradycardia likely plays a key role in seizure generation.